Real-World Experience With the SAPIEN 3 Ultra Transcatheter Heart Valve: A Propensity-Matched Analysis From the United States. (26th August 2021) - Nazif, Tamim M.; Cahill, Thomas J.; Daniels, David; McCabe, James M.; Reisman, Mark; Chakravarty, Tarun; Makkar, Raj; Krishnaswamy, Amar; Kapadia, Samir; Chehab, Bassem M.; Wang, John; Spies, Christian; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Paravalvular regurgitation (PVR) after transcatheter aortic valve replacement is associated with adverse clinical outcomes. The SAPIEN 3 Ultra (Ultra) is a new generation balloon-expandable transcatheter heart valve with a modified external skirt that is designed to reduce PVR, but reports of clinical and echocardiographic outcomes are limited. The aim of this study was to compare short-term outcomes of patients undergoing transcatheter aortic valve replacement with the Ultra and the original SAPIEN 3 (S3) transcatheter heart valve in a large national registry. Methods: Data from The Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry was used to compare patients who underwent elective, transfemoral transcatheter aortic valve replacement with the Ultra or S3 transcatheter heart valve. Clinical and echocardiographic outcomes were analyzed in a propensity-matched cohort at discharge and 30 days. Results: Patients who underwent transcatheter aortic valve replacement with Ultra (N=1324) from January 2019 to February 2020 were propensity score–matched with patients treated with S3 (N=32 982) during the same period, resulting in 1324 matched pairs. There was no difference in the rate of device success between patients treated with Ultra and S3 (97.1% versus 98.0%, P =0.11). At hospital discharge, PVR was significantly reduced with Ultra compared with S3, with mild PVR in 9.0% versus 13.9% and moderate or greater PVR in 0.1% versus 0.4% (overall P <0.01). At 30 days, there were no differences between Ultra and S3 recipients in the rates of all-cause mortality or stroke (1.8% versus 2.8%, P =0.10), major vascular complications (1.1% versus 1.0%, P =0.84), or permanent pacemaker implantation (6.4% versus 6.2%, P =0.81). Conclusions: In this propensity-matched analysis from the Transcatheter Valve Therapy Registry, the Ultra transcatheter heart valve was associated with similar procedural and 30-day clinical outcomes, but reduced incidence of PVR, compared with S3. The clinical benefit of less PVR should be evaluated in longer-term studies.